مصادر استهداف حوادث العمل لدى عمال الامن الصناعي في مؤسسة سوناطراك حاسي رمل - أوباتي زكريا; بن عروس بشرى نور الهدى; عون علي (My University, 2023)
The problem of this study was an attempt to identify the effectiveness of the approved and applied occupational health and safety procedures from the point of view of workers in the Department of Prevention and Occupational Safety (HSE) or the so-called industrial security, by limiting the procedures of the latter in this research to : - Providing occupational health and safety means. - Training courses for workers - Available health services - Counseling programmes. In order to address this problem, a direct field was used to control the research process and to reach consistent results in the field. The Directorate of Industrial Security of the Sonatrach Foundation, located in Hassi Rmel, was chosen as a place to conduct the field study, In order to satisfy the curiosity that was raised through a series of questions related to the study, one of the most important tools was relied upon to collect the information to be found, which was to design the questionnaire electronically and distribute it to the research sample consisting of 70 workers, and all questionnaires were retrieved, i.e. 100%. By following the steps of the descriptive approach, information was collected, cultured, and statistically processed, analyzed and interpreted, based on frequencies, percentages, and arithmetic averages. Finally, the results of the scientific study concluded that all procedures applied in the Industrial Security Directorate of Sonatrach in Laghouat - Hassi Ramel are effective from the point of view of workers. - Effectiveness of occupational health and safety means. - Effectiveness of training courses for workers. - An abundance of health services. - Effectiveness of extension programme